Cycling of phosphorus from wastewater to fertilizer using wood ash after energy production - Lee, Jae In; Jadamba, Chuluuntsetseg; Yoo, Soo Cheul; Lee, Chang Gu; Shin, Myung Chul; Lee, Jechan; Park, Seong Jik (Chemosphere, 2023)
Quercus wood was used for thermal energy production, and wood bottom ash (WDBA) was used as a medium for water purification and soil fertilizer in accordance with the recently proposed food-water-energy nexus concept. The wood contained a gross calorific value of 14.83 MJ kg−1, and the gas generated during thermal energy production has the advantage of not requiring a desulfurization unit due to its low sulfur content. Wood-fired boilers emit less CO2 and SOX than coal boilers. The WDBA had a Ca content of 66.0%, and Ca existed in the forms of CaCO3 and Ca(OH)2. WDBA absorbed P by reacting with Ca in the form of Ca5(PO4)3OH. Kinetic and isotherm models revealed that the results of the experimental work were in good agreement with the pseudo-second-order and Langmuir models, respectively. The maximum P adsorption capacity of WDBA was 76.8 mg g−1, and 6.67 g L−1 of WDBA dose could completely remove P in water. The toxic units of WDBA tested using Daphnia magna were 6.1, and P adsorbed WDBA (P-WDBA) showed no toxicity. P-WDBA was used as an alternative P fertilizer for rice growth. P-WDBA application resulted in significantly greater rice growth in terms of all agronomic values compared to N and K treatments without P. This study proposed the utilization of WDBA, obtained from thermal energy production, to remove P from wastewater and replenish P in the soil for rice growth.
Keywords: Bottom ash; Energy productions; Energy wood; Phosphorus fertilizer; Phosphorus removal; Quercus; Rice growths; Thermal energy production; Water purification; Wood ash; Adsorption; Coal Ash; Fertilizers; Phosphorus; Soil; Wastewater; Water; Hydroxyapatite; Phosphorus fertilizer; Phosphorus removal; Rice growth; Thermal energy production; Wood ash